Association of antibodies against myelin and neuronal antigens with neuroinflammation in systemic lupus erythematosus. (27th September 2018) - Pröbstel, Anne-Katrin; Thanei, Madlaina; Erni, Barbara; Lecourt, Anne-Catherine; Branco, Léonore; André, Raphaël; Roux-Lombard, Pascal; Koenig, Katrin F; Huynh-Do, Uyen; Ribi, Camillo; Chizzolini, Carlo; Kappos, Ludwig; et al.
Abstract: Objectives: To determine frequency and syndrome specificity of novel and known nervous system (NS)-directed antibodies in a large, unbiased cohort of SLE patients in the Swiss SLE Cohort Study. Methods: This retrospective pilot study included 174 patients in a cross-sectional and 102 in a longitudinal study. Antibodies against 12 NS antigens [myelin oligodendrocyte glycoprotein (MOG), neurofascin 186 (NF186), aquaporin-4 (AQP4), N -methyl-D-aspartate receptor (subunit NR1) (NMDAR-NR1), α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (subunits 1 and 2) (AMPAR1/2), gamma-aminobutyric acid B receptor (subunits B1 and B2) (GABABR1/2), glutamate decarboxylase 65 (GAD65), glycine receptor (GlyR), contactin-associated protein-like 2 (CASPR2), leucine-rich glioma-inactivated 1 (LGI1), metabotropic glutamate receptor 5 (mGluR5) and dipeptidyl-peptidase-like protein 6 (DPPX)] were screened with validated cell-based assays and correlated with clinical and diagnostic findings. Results: Twenty-three of one hundred and seventy-four (13.2%) patients harboured antibodies against MOG ( n = 14), NF186 ( n = 6), GAD65 ( n = 2), AQP4 and GlyR ( n = 1). Anti-MOG antibodies were most frequently found in the cohort (8%). Thirteen of the anti-NS antibody-positive patients showed clinical symptoms of NS involvement, a subgroup of which ( n = 8) resembled the syndrome associated with the antibody. Nine patients harboured antibodies without neurological symptoms and one patient was lost to follow-up. The frequency of NPSLE was significantly higher in the anti-NS antibody-positive patients (13/23, 56.5%: MOG 6/14, 42.9%; NF186 5/6, 83.3%; GAD65 2/2, 100%; AQP4/GlyR 0/1, 0%) compared with the antibody-negative cohort (21/151, 13.9%) (chi-square test, P < 0.0001). Conclusion: Anti-NS antibodies, most prevalently anti-MOG antibodies, are significantly associated with NPSLE and manifest with the distinct neurological syndrome associated with the antibody in a subgroup. Follow-up studies in large, independent cohorts will reveal whether these anti-NS antibodies could serve as a diagnostic and prognostic biomarker for NPSLE and enable tailored treatment decisions in this challenging and diverse patient cohort.